Botanical survey of ethnomedicines in Dayak sub-ethnic groups, Ot Danum and Tomum in Central Kalimantan, Indonesia - LISWARA NENENG; NAWAN NAWAN; FRANS GROVY NAIBAHO; SUDARMAN RAHMAN; LIA SEPTYA; DESIMARIA PANJAITAN; RIA WINDI LESTARI; ARIFIN SURYA DWIPA IRSYAM; NORWAHYUNIE NORWAHYUNIE; NORAINI NORAINI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Neneng L, Nawan, Naibaho FG, Rahman S, Septya L, Panjaitan D, Lestari RW, Irsyam ASD, Norwahyunie, Noraini. 2025. Botanical survey of ethnomedicines in Dayak sub-ethnic groups, Ot Danum and Tomum in Central Kalimantan, Indonesia. Biodiversitas 26: 458-469. The rise of globalization, urbanization, and environmental changes has led to the emergence of new infectious diseases and increased Antimicrobial Resistance (AMR), posing significant public health threats. This study aims to document the traditional medicinal knowledge of the Dayak Ot Danum and Tomum subtribes in Central Kalimantan, Indonesia, particularly regarding their ethnobotanical remedies for treating infectious diseases. Field surveys were conducted in August 2024 across four villages, utilizing purposive and snowball sampling techniques to interview 12 key informants, including traditional healers. Semi-structured interviews, Focus Group Discussions (FGD), and field observations were employed to gather information on the local use of medicinal plants. A total of 62 plant species were identified, with the highest proportions targeting bacterial infections (24 species), followed by viral (21 species), fungal (11 species), and parasitic infections (4 species), with mixed efficacy as antibacterial and antifungal (10 species) and antibacterial and antiviral (3 species). The Zingiberaceae family was the most frequently documented, a testament to the diverse and rich ethnobotanical knowledge of these communities. The findings highlight the effective use of traditional medicine in combating infections, suggesting the potential for integrating ethnobiological practices into contemporary healthcare strategies to address AMR. As indigenous populations face increasing health risks, preserving and leveraging traditional medicinal knowledge is crucial for developing sustainable approaches to health and wellness.